(untitled) (Development Service Industry Management, 2023)
Modern economic conditions are characterized by the instability of the energy sector, the increase in the cost of energy carriers, the strengthening of environmental restrictions, as well as geopolitical risks that create significant challenges for enterprises. In such conditions, effective management of energy security becomes a key element of competitiveness, sustainable development and economic stability of enterprises. The integration of organizational and economic mechanisms in the energy security management system makes it possible to increase the efficiency of resource use, reduce the energy dependence of enterprises, ensure their adaptability to a changing environment, and minimize the risks associated with energy crises. The purpose of the article is the formation of a theoretical basis for the organizational and economic support of energy security management of enterprises. The approaches of various authors to the definitions of the concepts of "organizational support", "economic support", "management", "security", "energy security" have been studied. The author’s definitions of the mentioned concepts are offered. The theoretical foundation of the organizational and economic support for energy security management of enterprises is offered, the main components of which are organizational support, economic support, management, security and energy security. Organizational support is aimed at creating structural order and coordination of activities, while economic support forms the financial base necessary for the implementation of energy security strategies. In combination with management functions such as planning, organization, motivation and control, it contributes to achieving a comprehensive solution to the issues of protecting the energy resources of the enterprise.